Onboard carbon capture, utilization, and storage - Wu,J; Zhang,Y; Jiang,M; Cao,XE; Zhang,Z (Cell Reports Physical Science, 2026)
Carbon capture, utilization, and storage (CCUS) represents a key carbon-reduction strategy with significant potential to address global climate change. Current research primarily focuses on mitigation approaches for large-scale terrestrial emitters, such as power plants and petrochemical facilities, whereas comprehensive reviews in the maritime sector remain relatively scarce. In particular, there is a lack of studies that synthesize international development experiences or explore future trends aimed at meeting increasingly stringent carbon-reduction requirements in shipping. This paper reviews the current state of shipboard carbon-capture systems worldwide and emphasizes that real-time onboard CO2 processing and utilization is likely to emerge as a critical pathway for decarbonizing the shipping industry. Given the distinct composition of marine exhaust gases and the challenges associated with integrating CCUS systems on vessels, future efforts should prioritize integrated system design. Moreover, dedicated technological development adapted to the maritime environment is essential to advance ship-based CCUS solutions.